The modern concept of international legal responsibility - Zhukorska, Yaryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
The author attempts to explore the features of the modern concept of international responsibility in the article. The historical basis of the emergence and formation of the institution of responsibility, current trends in its development are analyzed. The development of the concept of international responsibility from its emergence to the concept of objective responsibility, which formed the basis of the Articles on States’ Responsibility for International and Unlawful Actions, developed by the CIL are explored. The modern institute of international responsibility is developing very fast and is being actively codified are emphasized. The current areas of its codification and research are the responsibility of international organizations and succession to the responsibility of states.